Climate sensitivity and meridional overturning circulation in the late Eocene using GFDL CM2.1 - D. K. Hutchinson; A. M. de Boer; H. K. Coxall; R. Caballero; J. Nilsson; M. Baatsen (Climate of the Past, 2018)
The Eocene–Oligocene transition (EOT), which took place approximately 34 Ma ago, is an interval of great interest in Earth's climate history, due to the inception of the Antarctic ice sheet and major global cooling. Climate simulations of the transition are needed to help interpret proxy data, test mechanistic hypotheses for the transition and determine the climate sensitivity at the time. However, model studies of the EOT thus far typically employ control states designed for a different time period, or ocean resolution on the order of 3°. Here we developed a new higher resolution palaeoclimate model configuration based on the GFDL CM2.1 climate model adapted to a late Eocene (38 Ma) palaeogeography reconstruction. The ocean and atmosphere horizontal resolutions are 1° × 1.5° and 3° × 3.75° respectively. This represents a significant step forward in resolving the ocean geography, gateways and circulation in a coupled climate model of this period. We run the model under three different levels of atmospheric CO 2 : 400, 800 and 1600 ppm. The model exhibits relatively high sensitivity to CO 2 compared with other recent model studies, and thus can capture the expected Eocene high latitude warmth within observed estimates of atmospheric CO 2 . However, the model does not capture the low meridional temperature gradient seen in proxies. Equatorial sea surface temperatures are too high in the model (30–37 °C) compared with observations (max 32 °C), although observations are lacking in the warmest regions of the western Pacific. The model exhibits bipolar sinking in the North Pacific and Southern Ocean, which persists under all levels of CO 2 . North Atlantic surface salinities are too fresh to permit sinking (25–30 psu), due to surface transport from the very fresh Arctic ( ∼ 20 psu), where surface salinities approximately agree with Eocene proxy estimates. North Atlantic salinity increases by 1–2 psu when CO 2 is halved, and similarly freshens when CO 2 is doubled, due to changes in the hydrological cycle.